Look Inside a Train How It Works - Leed, Percy (Minneapolis, MN Lerner Publications, 2024)
"All aboard! From transporting cargo to helping people travel, trains play an important role in everyday life. Readers take a look inside trains to discover their parts and the science behind how they work"--
Make way for trains -- Trains at work -- On the tracks -- Cool parts -- Train diagram -- Powering trains -- Glossary.
Includes bibliographical references and index.
Ages 6-9
Grades 2-3
112961
Keywords: Railroad trains; Trains; Transportation; Juvenile works